Large Eddy Simulation of liquid sheet breakup using a two-phase lattice Boltzmann method. (4th January 2018) - Amirshaghaghi, Hadi; Rahimian, Mohammad Hassan; Safari, Hesameddin; Krafczyk, Manfred
Highlights: A novel two-phase LES model is developed within the framework of phase-field LBM. The developed model is straightforward to implement. Using the developed model turbulent liquid sheet breakup is studied. Abstract: A two-phase flow Large Eddy Simulation (LES) model is developed within the framework of phase-field lattice Boltzmann methods (LBM). The proposed model is based on a standard Smagorinsky model for subgrid closure and uses the Multiple-Relaxation-Time (MRT) collision operator. Relevant test cases are considered to demonstrate the capability and accuracy of the new model in dealing with two-phase flows at wide range of density contrasts. These include the Rayleigh–Taylor instability at two distinct density ratios, the breakup of a turbulent liquid column, and assisted breakup of a liquid layer. The validated model is then utilized to examine a liquid sheet emerging from a nozzle into a stagnant gas at different Reynolds numbers ranging from 1000 to 6000. The influence of jet injection velocity on the flow structure, variation of the jet centerline velocity, and jet area is also investigated. This work reports for the first time the extension of the Smagorinsky model for LES to the binary fluid model of Fakhari & Lee[1] and its application in simulation of turbulent liquid sheet breakup at the density ratios as high as 250.